Studi Komprehensif Destination Image, Service Quality, Dan Visitor Experience Di Jakarta Aquarium Safari: Pengaruhnya Terhadap Visitor Satisfaction Dan Revisit Intention - Arini Tazkia Putri Indana; Usep Suhud; Meta Bara Berutu (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to identify the influence of destination image, visitor experience, and service quality on visitor satisfaction and revisit intention at Jakarta Aquarium Safari. All five variables were tested to derive research findings. This research employs a quantitative approach using Structural Equation Modeling (SEM). Primary data was collected through a questionnaire utilizing a Likert scale ranging from strongly agree to strongly disagree. The sample characteristics involve tourists aged 18-30 from the Jabodetabek area who have visited Jakarta Aquarium Safari at least once. Purposive sampling was chosen to obtain a sample resulting in no less than 211 respondents. The results of this study indicate that destination image and service quality significantly have a direct impact on visitor satisfaction, while visitor experience and visitor satisfaction significantly have a direct impact on revisit intention. However, visitor experience does not have a significant influence on visitor satisfaction.